The EU and the domestic politics of welfare state reforms. Europa, Europae - Graziano, Paolo; Jacquot, Sophie; Palier, Bruno (New York, 2011)
"Does European integration influence national social policies? What is the use of EU laws, orientations and guidelines? Based on a systematic comparison of ten national cases, including both old and new member states, representing all families of welfare regimes, this volume explores and specifies the mechanisms through which the EU plays a role in domestic social policy changes. It focuses on where, when and how national actors use the tools and resources offered by the process of European integration to support them in the national welfare reforms they are engaged in. The comprehensive research design and the systematic comparisons provide a unique opportunity to fully grasp the mechanisms of domestic welfare state change within the context of the European Union multilevel political system. This book proposes both a new step within the Europeanization and the welfare state literatures. It confirms the idea that Europe matters in a differential way since EU social policy will be selectively used by domestic political actors in accordance with their political preferences. It provides a clear explanation of why no EU-induced social policy change can occur without an overall support offered by key domestic decision-makers."